2015
DOI: 10.1039/c4ta05462h
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene elastomer composite for the all-vanadium redox flow battery: current collector materials

Abstract: ARTICLE This journal isIn this study, carbon-based polypropylene thermoplastic elastomer (PP-elastomer) composite for current collectors of all-vanadium redox flow battery (VRB) was successfully prepared. The volume resistivity of the PP-elastomer composite was 0.47 Ω·cm. Its tensile strength and elongation at break were 6.6 MPa and 250%, respectively. In addition, good flow property in processing makes this composite has the potential on mass industrial production of current collectors. The single cell and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…6,16,25 Electrochemical oxidation is caused by potential differences in the cells of a VRFB leading to damage of BPPs. 4 Corrosion may cause an increase in the porosity 7,16,21 leading to ion permeability, brittleness, loss in mechanical stability and a decreased electrical conductivity. It was reported that the shunt current might play the main role in this process whereas the main current is less dominant.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…6,16,25 Electrochemical oxidation is caused by potential differences in the cells of a VRFB leading to damage of BPPs. 4 Corrosion may cause an increase in the porosity 7,16,21 leading to ion permeability, brittleness, loss in mechanical stability and a decreased electrical conductivity. It was reported that the shunt current might play the main role in this process whereas the main current is less dominant.…”
mentioning
confidence: 99%
“…While vanadium redox reactions mainly occur on the surfaces of the porous electrodes, they could also occur unintentionally on the surfaces of the BPPs. [5][6][7] Therefore, a good BPP should be characterized by a high chemical and mechanical stability, high electrical conductivity and impermeability to preclude leakage. 8 Metallic BPPs are usually not used in VRFB as they corrode in acidic environments and would need a protective layer.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16] For example, after applying over 2300 charging/discharging cycles in a cell stack with BPPs containing carbon fibers/carbon black-polypropylene composite, the BPPs had developed local blisters and a rougher surface indicating slight corrosion of the plates during VRFB stack operation. 15 There are two main reasons for occurrence of corrosive overpotentials in the stack. Firstly, they can appear due to shunt or parasitic currents, for example through an electric contact of the positive electrolyte with BPPs of different potentials in the in-/outlet channels of the half-cells.…”
mentioning
confidence: 99%